2022
DOI: 10.1039/d1tc05010a
|View full text |Cite
|
Sign up to set email alerts
|

Benzonitrile-based AIE polymer host with a simple synthesis process for high-efficiency solution-processable green and blue TADF organic light emitting diodes

Abstract: Polymer host material have great potential for enable small molecular thermally activated delayed fluorescence (TADF) emitters to construct solution-processed organic light-emitting diodes (OLEDs). Herein, four novel benzonitrile-based polymer host, P4CzCN-PA,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Additionally, the L values of the patterned SI-OLEDs were slightly reduced compared to those of the non-patterned SI-OLEDs, which could be attributed to the (i) reduced effective light-emitting area (6 µm × 6 µm) owing to the deposited PDL and (ii) inevitable exposure to O 2 and H 2 O during the RCP process. However, the V on and L characteristics of the patterned SI-OLEDs were comparable to those of previous studies on solution-processable, non-patterned, polymer-based, thermally activated delayed fluorescence OLEDs or perovskite light-emitting diodes 36 38 .
Fig.
…”
Section: Resultssupporting
confidence: 83%
“…Additionally, the L values of the patterned SI-OLEDs were slightly reduced compared to those of the non-patterned SI-OLEDs, which could be attributed to the (i) reduced effective light-emitting area (6 µm × 6 µm) owing to the deposited PDL and (ii) inevitable exposure to O 2 and H 2 O during the RCP process. However, the V on and L characteristics of the patterned SI-OLEDs were comparable to those of previous studies on solution-processable, non-patterned, polymer-based, thermally activated delayed fluorescence OLEDs or perovskite light-emitting diodes 36 38 .
Fig.
…”
Section: Resultssupporting
confidence: 83%
“…16). 161 All the developed hosts had high triplet energies of ∼2.68 eV and aggregation-induced emission properties. All the developed polymers were capable of trapping excitons and preventing exciton quenching.…”
Section: Reaction Chemistry and Engineering Reviewmentioning
confidence: 99%
“…Hu et al reported a through-space charge-transfer polymer containing a nonconjugated polystyrene backbone, and the maximum external quantum efficiencies (EQE max ) of deep-blue-, green-, and white-emitting solution-processed OLEDs were 7.1%, 16.2%, and 14.1%, respectively. Thus, this simple synthesis of a nonconjugated polystyrene-based chain polymer does show great potential for solution processing of OLEDs. However, most of the polymers are simply applied to glass substrates, and very few attempts have been made for flexible substrates. Danyliv et al prepared a small-molecule CzPrSBI using sulfobenzimide as an acceptor, and EQE max of the nondoped TADF emitter was only 0.9% in a flexible OLEDs prepared on a poly­(ethylene terephthalate) (PET) substrate using vacuum vapor deposition .…”
Section: Introductionmentioning
confidence: 99%